Comparative rheological evaluation of associative thickeners in water-based paint: Influence of polymeric binder and thickener concentration - Cibangwa M.K; Ikhu-Omoregbe D; Nomnqa M (Case Studies in Chemical and Environmental Engineering)
This study investigates the rheological and optical performance of water-based paints using Hydrophobically Modified Ethoxylated Urethane (HEUR) and Hydrophobically Modified Alkali Swellable Emulsions (HASE) as thickeners with styrene acrylic (SA) and pure acrylic (PA) binders. Novel insights include the superior thickening efficiency and elasticity of HASE with PA binders, while HEUR maintained consistent performance across binders. Importantly, a correlation between rheology and optical attributes such as gloss and opacity has been established, highlighting rheology's critical role in optimizing paint formulations for application and aesthetic performance. This study bridges the gap in understanding binder-thickener interactions in decorative paints.